Jesus y la Samaritana: una lectura de Jn 4,5-26 - Peirano, Ana Maria Casarotti (2011)
This paper provides an analysis of the encounter between Jesus and a Samaritan woman at the edge of Jacob s well as it is narrated in the Gospel of John 4,5-26. The first chapter examines the historical and socio-religious gospel text with special attention to the historical three pairs, which are: The rivalry between Jews and Samaritans; water as both a religious and a life element in contrast with the living water given by Jesus, and the historical journey of the patriarchal society in relation with women before the thought given by Jesus in the Gospel. The second chapter examines the present text drawing upon the historical-critical method, focusing in the semantic study of certain words and the dialogue between Jesus and the Samaritan woman that enrich their understanding. The contribution of extra-biblical traditions provides deeper insights of the text. The third chapter brings a theological-pastoral reflection over the analyzed text from the perspective of the encounter. The living water that Jesus offered suggests the imperfection of the previous waters that until then mediated the relationship with God. The Samaritan woman's encounter with Jesus through dialogue and progress deepens the originality of the Gift offered. We study its characteristics and its consequences. The fourth chapter presents the challenges provided by this text to the current culture emphasizing the need for an open dialogue to diversity. It outlines the need for recognition of the place of women in contemporary society, with emphasis on the religious arena. The conclusion opens up new questions and commitments signed out on the text: the need to continue walking toward a discipleship of equals as the foundation and essence of a Christian community that wants to live up to Jesus, and the necessary recognition of the place of women in contemporary society, with emphasis on the religious sphere.